Dividends And Value Of The Firm : A Study Of The Malaysian Corporate Sector - Kok, Lee Kuin (2003)
This study analyses the Corporate Dividend Policies in Malaysia, an emerging capital market in Asia Pacific region with two-fold objective through the following hypotheses: 1) To examine the Corporate Dividend Behaviour. 2) To verify the Miller and Modigliani's Dividend Irrelevance Hypothesis.